Evaluación del desplazamiento sísmico un edificio de 10 pisos en Yopal de un sistema de muros industrializados mediante análisis estático no lineal (2020)
The objective of this report is to present the procedures and methodologies used in the analysis and structural design of a 10-story reinforced concrete building, located in the city of Yopal. These analyzes and designs were elaborated with the terms and conditions present in the Colombian Regulation of Design and Construction Resistant Earthquake NSR-10. In order to ensure the stability and proper functioning of the structure. Figure 1 illustrates the project of the model in ETABS.